Magnesium powder injection moulding for biomedical application. (December 2014) - Wolff, M.; Schaper, J. G.; Dahms, M.; Ebel, T.; Kainer, K. U.; Klassen, T.
Abstract : Currently, commercial biodegradable implants are mainly made from degradable polymers, such as polyglycolic acid or polylactide acid (PLA). These polymer implants, produced by injection moulding technique, suffer from long degradation times between 18 and 36 months, poor mechanical properties and acidic degradation behaviour. On the other hand, magnesium alloys are drawing increasing interest as biodegradable medical implant material for orthopaedic applications in bone tissue; thus, a replacement of polymers by Mg would be attractive. The production of biomedical and biodegradable Mg alloy parts and implants by powder metallurgy and metal injection moulding (MIM) respectively offers the opportunity for economic manufacturing of parts with mechanical properties matching those of cortical bone tissue, as well as the provision of porous surface structures beneficial for cell ingrowth and vascularisation. Furthermore, the technique guarantees a homogenous microstructure being crucial for a predictable degradation process. This study shows how magnesium powder can be processed successfully by MIM. Recent magnesium alloy implant prototypes and tensile test specimen, produced by MIM technique, provide strength and stiffness twice as high compared to modern polymer based implants. Ultimate tensile strength (UTS) of 131 MPa, yield strength of 64 MPa, residual porosity of 2–6% and elastic modulus of 46 GPa, measured by dynamic method, were achieved under application of special sintering technique and sintering atmosphere control. The paper is focussing on sintering methods and porosity control and measurement.